2004
DOI: 10.1091/mbc.e03-12-0872
|View full text |Cite
|
Sign up to set email alerts
|

Autoantigen Golgin-97, an Effector of Arl1 GTPase, Participates in Traffic from the Endosome to theTrans-Golgi Network

Abstract: The precise cellular function of Arl1 and its effectors, the GRIP domain Golgins, is not resolved, despite our recent understanding that Arl1 regulates the membrane recruitment of these Golgins. In this report, we describe our functional study of Golgin-97. Using a Shiga toxin B fragment (STxB)-based in vitro transport assay, we demonstrated that Golgin-97 plays a role in transport from the endosome to the trans-Golgi network (TGN). The recombinant GRIP domain of Golgin-97 as well as antibodies against Golgin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
149
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(161 citation statements)
references
References 65 publications
11
149
0
1
Order By: Relevance
“…We investigated whether ARL1 colocalised with Gm130 as well as TPD52. As expected (Lu et al, 2004), ARL1 showed incomplete peri-nuclear colocalisation with Gm130 in D52-2-7 cells with or without oleic acid treatment (Fig. 5A), and in vector control cells (supplementary material Fig.…”
Section: Colocalisation Of Tpd52 With Arl1 On Golgi In Tpd52-expressisupporting
confidence: 82%
“…We investigated whether ARL1 colocalised with Gm130 as well as TPD52. As expected (Lu et al, 2004), ARL1 showed incomplete peri-nuclear colocalisation with Gm130 in D52-2-7 cells with or without oleic acid treatment (Fig. 5A), and in vector control cells (supplementary material Fig.…”
Section: Colocalisation Of Tpd52 With Arl1 On Golgi In Tpd52-expressisupporting
confidence: 82%
“…These observations are in line with recent studies suggesting that GRIP domain-containing golgins and Arl1 participate in trafficking from endosomes to the TGN Yoshino et al, 2003) and with previous yeast data indicating that Arl1p genetically and biochemically interact with components of protein machineries that function in the endosome-to-late Golgi trafficking pathway, such as the Ric1p/Rgp1p complex, Ypt6p and the GARP/VFT complex (Bensen et al, 2001;Panic et al, 2003b). GRIP domaincontaining golgins have been suggested to be tethering molecules on trans-Golgi/TGN membranes (Barr and Short, 2003;Gillingham and Munro, 2003;Lu and Hong, 2003;Lu et al, 2004) in mammalian cells. Furthermore, Imh1p/Sys3p, the sole GRIP domain-containing golgin in yeast, has been suggested to function in vesicle docking in the endosome-tolate Golgi retrograde trafficking (Tsukada et al, 1999).…”
Section: Discussionsupporting
confidence: 52%
“…Fig. 5 reports immunodetection of Golgi complex by anti-golgin 97 antibody that recognizes the 97 kDa protein golgin-97, a peripheral membrane protein localized on the cytoplasmic face of the Golgi apparatus, that plays a critical role in vesicle traffic from the endosome to the trans-Golgi network (39). SH-SY5Y cells cultured onto the flat surface (Fig.…”
Section: Resultsmentioning
confidence: 99%